Implementation Analysis of Medan City Regional Regulation No. 3 of 2014 on Smoke-Free Areas in Medan Baru District - Manurung, Jasmen; Sinaga, Lia Rosa Veronika; Munthe, Seri Asnawati; Bangun, Henny Arwina (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
The Medan City Government has enacted Regional Regulation No. 3 of 2014 concerning Smoke-Free Areas (SFA) to protect the public from exposure to tobacco smoke in public facilities. However, its implementation remains inconsistent across sectors and compliance remains low. This study aims to analyze the implementation of SFA regulations in Medan Baru District, Medan City, using William C. Edwards III's policy implementation framework, which focuses on communication, resources, disposition, and bureaucratic structure. Informants were determined purposively, representing implementers, supervisors, and policy targets. The SFA regulation has been socialized but not consistently. Limited human resources, insufficient budget, irregular monitoring, and the lack of SFA signage are weaknesses in implementing the SFA regulation. Policy implementers understand the policy objectives but remain weak in commitment. The bureaucratic structure, although the division of tasks between agencies is clear on paper, suffers from weak inter-agency coordination, SOP compliance, and law enforcement. Commitment from all parties is required to implement the SFA regulation in Medan City, as almost all sectors still have weaknesses in its implementation. Keywords: SFA Regulation, Policy Implementation, William C. Edwards III, Medan City